(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article analyzes the place and significance of symbolism in the tragic works of William Shakespeare. The article examines the dramatic, psychological, and thematic role of characters in Shakespeare’s major tragedies, including Hamlet, Othello, King Lear, Macbeth, and Romeo and Juliet. It discusses in detail how symbolism increases the depth of tragedy, expresses themes, and enhances the emotional impact of the audience. The article examines the development of symbolism in the context of Shakespeare’s work.